The Roles of Farmers in the Development of Belimbing Village Agrotourism and Its Effect on Satisfaction and Loyalty of Tourists - Widari, Ni Nyoman; Suryawardani, I Gusti Ayu Oka; Rantau, I Ketut; Wiranatha, Agung Suryawan (E-Journal of Tourism; Volume 7 Number 1 (March 2020), 2020)
Belimbing Village Agrotourism is an agriculture-based sustainable agrotourism that has extensive terraced rice fields and stretches with a variety of natural potential around. Development of Belimbing Village Agrotourism is a tourism activity without changing the use and damage of agricultural land and can help the economy of the community in Belimbing Village. This study aims to determine the effect of farmers' knowledge, farmers' skills and farmers' attitudes on the satisfaction of Belimbing Village Agrotourism, the effect of tourists’ satisfaction on visitor loyalty visiting Belimbing Village Agrotourism and Belimbing Village Agrotourism contribution to the welfare of the community in Belimbing Village. Data analysis method used is quantitative and qualitative analysis methods. The population in this study were farmers in Belimbing Village Agrotourism and tourists visiting Belimbing Village Agrotourism using 60 respondents, 30 people for farmers and 30 people for tourists. The model was designed using a Smart PLS-based Structural Equation Modeling (SEM) approach that was analyzed using a computer. The results showed that farmers' knowledge had a significant influence on tourists’ satisfaction (p = 0.031). Farmer skills have a significant influence on tourist satisfaction (p = 0.024). Farmer's attitude has a significant effect on tourist satisfaction (p = 0,000). Tourist satisfaction has a significant effect on tourist loyalty (p = 0,000). The contribution of the Belimbing Village Agrotourism in terms of economy, environment and social has a positive impact on the welfare of the community in the Belimbing Village. Based on the results of the study, it is hoped that the Belimbing Village Agrotourism can maintain and improve farmers' knowledge, farmers' skills and farmers' attitudes, so that visiting tourists are satisfied and generate tourist loyalty to visit again. Keywords: Role of Farmers, Agrotourism Development, Tourists’ Satisfaction, Tourists’ Loyalty